Debitoru parādu pārvaldība kā līdzeklis, lai uzlabotu uzņēmējdarbības rezultātus - Tadjitdinov, Jasur (Latvijas Universitāte, 2019)
Bakalaura «Debitoru parādu pārvaldība kā līdzeklis, lai uzlabotu uzņēmējdarbības rezultātus». Darba autors: Jasur Tadjitdinov. Zinātniskais vadītājs: Dr.Oec., Margarita Dunska. Darbs « Biznesa, vadības un ekonomikas fakultāte » grāda iegūšanai: 87 lpp., 21att., 17 tab., 28 izmantotās lit. avot. Kursa mērķis ir izstrādāt notikumu, lai pārvaldītu debitoru parādus, lai uzlabotu uzņēmuma efektivitāti. Lai sasniegtu šo mērķi, tika izvirzīti šādi uzdevumi: • izpētīt konta debitoru parādu teorētiskos aspektus un to novērtēšanas metodes; • sniegt īsu tirdzniecības aprakstu uzņēmumam Ai-syrem grand trade; • Veikt uzņēmuma Ai-syrem grand tirdzniecības finanšu rādītāju analīzi; • Izstrādāt priekšlikumus uzņēmuma debitoru parādu pārvaldībai • Ai-syrem grand trade; • izdarīt secinājumus par paveikto darbu un izstrādāt ieteikumus uzņēmumam Aisyrem grand trade. Kursa darba struktūra sastāv no atsaucēm, trim nodaļām, secinājumiem un ieteikumiem. Pirmajā nodaļā ir norādīti debitoru parādu teorētiskie aspekti un to novērtēšanas metodes. Otrajā daļā analizējam uzņēmuma Ai-syrem finanšu rezultātus. Šī uzņēmuma Ai-syrem analīzei tiek izstrādāti pasākumi debitoru parādu pārvaldībai. Secinājumi ir izdarīti un ieteikumi ir sagatavoti "Ai-syrem grand trade". ATSLĒGVĀRDI: KONTA SAŅĒMUMI, KREDĪTI, ANALĪZE, FAKTORIJA

The theme of the Bachelor thesis is « Debtor management as a tool of enhancing business performance ». Author of the bachelor thesis: Jasur Tadjitdinov. Scientific supervisor: Dr.Oec., professor Margarita Dunska. Paper for obtaining the degree «Bachelor of Business, Management and Economics»: 87 pp., 21 fig., 17 tables, 28 ref. The purpose of the thesis is to develop an event to manage accounts receivable to improve the efficiency of the enterprise. To achieve this goal, the following tasks were set:  To study the theoretical aspects of account receivables and methods for its assesment;  To give a short trade description of the enterprise Ai-syrem grand trade;  Conduct analysis of financial indicators of the enterprise Ai-syrem grand trade;  Develop proposals for management of accounts receivable for the enterprise  Ai-syrem grand trade;  Make conclusions on the work done and develop recommendations for the enterprise Ai-syrem grand trade. The structure of the bachelor work consists of reference, three chapters, conclusions and recommendations. The first chapter indicates the theoretical aspects of receivables and methods for evaluating it. In the second part, we analyze the financial performance of the company Ai-syrem. Accornig to this analysis of the company Ai-syrem, measures are being developed to manage accounts receivable. Conclusions are made and recommendations are drawn for OOO " Ai-syrem grand trade ". KEYWORDS: ACCOUNT RECEIVABLES, CREDITS, ANALYSIS, FACTORING.
Debtor management as a tool of enhancing business performance
Keywords: Vadībzinātne; ACCOUNT RECEIVABLES; CREDITS; ANALYSIS; FACTORING